Solar Vapor‐Generation: Carbonized Bamboos as Excellent 3D Solar Vapor‐Generation Devices (Adv. Mater. Technol. 4/2019). Issue 4 (16th April 2019) - Bian, Yue; Du, Qianqian; Tang, Kun; Shen, Yang; Hao, Licai; Zhou, Dong; Wang, Xiaokun; Xu, Zhonghua; Zhang, Huiling; Zhao, Lijuan; Zhu, Shunming; Ye, Jiandong; et al.
Abstract : Carbonized bamboos have been utilized as solar‐vapor generation devices in article number1800593 by Yue Bian, Kun Tang, Shulin Gu and co‐workers. Such a hidden talent of bamboo is achieved by the hierarchically nanostructured mesh and the 3D macroscopic structure. This work could enlighten more biomimetic solar evaporator designs, aiming to tackle freshwater scarcity in a green and sustainable way.